The White Possessive : Property, Power, and Indigenous Sovereignty - Moreton-Robinson, Aileen (Book collections on Project MUSE., 2015)
"The White Possessive explores the links between race, sovereignty, and possession through themes of property: owning property, being property, and becoming propertyless. Focusing on the Australian Aboriginal context, Aileen Moreton-Robinson questions current race theory in the first world and its preoccupation with foregrounding slavery and migration. The nation, she argues, is socially and culturally constructed as a white possession. Moreton-Robinson reveals how the core values of Australian national identity continue to have their roots in Britishness and colonization, built on the disavowal of Indigenous sovereignty. Whiteness studies literature is central to Moreton-Robinson's reasoning, and she shows how blackness works as a white epistemological tool that bolsters the social production of whiteness--displacing Indigenous sovereignties and rendering them invisible in a civil rights discourse, thereby sidestepping thorny issues of settler colonialism. Throughout this critical examination Moreton-Robinson proposes a bold new agenda for critical Indigenous studies, one that involves deeper analysis of how the prerogatives of white possession function within the role of disciplines."--